Assessment of Competency of Point-of-Care Ultrasound in Emergency Medicine Residents during Ultrasound Rotation at the Emergency Department - Apiratwarakul, Korakot; Ienghong, Kamonwon; Tongthummachat, Nichaphat; Suzuki, Takaaki; Tiamkao, Somsak; Bhudhisawasdi, Vajarabhongsa (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Point-of-care ultrasound (POCUS) is the core competency in the Emergency Medicine (EM) residency training. However, there are many methods that can be used to evaluate this competency, and the best practices for teaching ultrasonography to residents have yet to be determined. AIM: The researchers aimed at evaluating the POCUS knowledge and skills of the EM residents after having participated in the POCUS training during their first ultrasound rotation in the Emergency Department. METHODS: A curriculum was developed in the form of a 2-week rotation in the EM residency program at the Department of EM at Khon Kaen University’s Srinagarind Hospital. It consisted of didactic lectures, bedside ultrasound trainings, the journal club, and the process of reviewing the images. Tools were developed, which included a knowledge exam. For each resident, the assessments were administered before and after the rotation. Furthermore, an ultrasound skills test was developed to be used at the end of the 1st year EM residency program. RESULTS: Nine EM residents completed their rotations and the tests. The average pre-training score and post-training scores were 5.25 ± 1.03 and 8.50 ± 1.20, respectively. The mean difference score between pre- and post-test was 3.25 ± 1.28. (95% CI −4.321, −2.178). In terms of the ultrasound skills test, the average total score was 26.13 out of 30 (87.1%). Moreover, the residents had higher scores in the aspects of image acquisition (87.5%) and image interpretation (87.5%). However, for the aspect of clinical decision-making, the average score was 75%. The survey questions indicated that with respect to all of the academic activities, the “Bedside ultrasound,” which had encouraged the residents to learn POCUS, was given the highest score (4.75 of 5). CONCLUSIONS: The 2-week ED ultrasound rotation had improved the residents’ EM ultrasound knowledge and skills.